Cell-Free Protein Synthesis with Fungal Lysates for the Rapid Production of Unspecific Peroxygenases - Marina Schramm; Stephanie Friedrich; Kai-Uwe Schmidtke; Jan Kiebist; Paul Panzer; Harald Kellner; René Ullrich; Martin Hofrichter; Katrin Scheibner (MDPI AG, 2022)
Unspecific peroxygenases (UPOs, EC 1.11.2.1) are fungal biocatalysts that have attracted considerable interest for application in chemical syntheses due to their ability to selectively incorporate peroxide-oxygen into non-activated hydrocarbons. However, the number of available and characterized UPOs is limited, as it is difficult to produce these enzymes in homologous or hetero-logous expression systems. In the present study, we introduce a third approach for the expression of UPOs: cell-free protein synthesis using lysates from filamentous fungi. Biomass of Neurospora crassa and Aspergillus niger, respectively, was lysed by French press and tested for translational activity with a luciferase reporter enzyme. The upo1 gene from Cyclocybe (Agrocybe) aegerita (encoding the main peroxygenase, AaeUPO) was cell-free expressed with both lysates, reaching activities of up to 105 U L−1 within 24 h (measured with veratryl alcohol as substrate). The cell-free expressed enzyme (cfAaeUPO) was successfully tested in a substrate screening that included prototypical UPO substrates, as well as several pharmaceuticals. The determined activities and catalytic performance were comparable to that of the wild-type enzyme (wtAaeUPO). The results presented here suggest that cell-free expression could become a valuable tool to gain easier access to the immense pool of putative UPO genes and to expand the spectrum of these sought-after biocatalysts.